Global economic burden of diabetes in adults: projections from 2015 to 2030 - Bommer, Christiane Friederike; Sagalova, Vera; Heesemann, Esther; Manne-Goehler, Jennifer; Atun, Rifat; Bärnighausen, Till; Davies, Justine; Vollmer, Sebastian (Diabetes care, 2018)
OBJECTIVE Despite the importance of diabetes for global health, the future economic consequences of the disease remain opaque. We forecast the full global costs of diabetes in adults through the year 2030 and predict the economic consequences of diabetes if global targets under the Sustainable Development Goals (SDG) and World Health Organization Global Action Plan for the Prevention and Control of Noncommunicable Diseases 2013-2020 are met. - RESEARCH DESIGN AND METHODS We modeled the absolute and gross domestic product (GDP)-relative economic burden of diabetes in individuals aged 20-79 years using epidemiological and demographic data, as well as recent GDP forecasts for 180 countries. We assumed three scenarios: prevalence and mortality 1) increased only with urbanization and population aging (baseline scenario), 2) increased in line with previous trends (past trends scenario), and 3) achieved global targets (target scenario). - RESULTS The absolute global economic burden will increase from U.S. $1.3 trillion (95% CI 1.3-1.4) in 2015 to $2.2 trillion (2.2-2.3) in the baseline, $2.5 trillion (2.4-2.6) in the past trends, and $2.1 trillion (2.1-2.2) in the target scenarios by 2030. This translates to an increase in costs as a share of global GDP from 1.8% (1.7-1.9) in 2015 to a maximum of 2.2% (2.1-2.2). - CONCLUSIONS The global costs of diabetes and its consequences are large and will substantially increase by 2030. Even if countries meet international targets, the global economic burden will not decrease. Policy makers need to take urgent action to prepare health and social security systems to mitigate the effects of diabetes.